Characterization and bioefficacy of grapevine bacterial endophytes against Colletotrichum gloeosporioides causing anthracnose disease - Holkar, Somnath K.; Bhanbhane, Vrushali C.; Ghotgalkar, Prabhavati S.; Markad, Harshavardhan N.; Lodha, Tushar D.; Saha, Sujoy; Banerjee, Kaushik (Frontiers in Microbiology, 2024)
IntroductionGrapevine (Vitis vinifera L.), one of the economically important fruit crops cultivated worldwide, harbours diverse endophytic bacteria (EBs) responsible for managing various fungal diseases. Anthracnose (Colletotrichum gloeosporioides) (Penz.) is one of the major constraints in quality grape production and therefore its management is a major concern among the grape growers.Materials and methodsAmong the 50 EBs isolated from healthy leaf segments from the eight grapevine genotypes, biologically potential 20 EBs were purified and identified based on morphological, and biological characteristics and sequence analysis of 16S rRNA region. The antagonistic activities of EBs against Colletotrichum gloeosporioides were studied in vitro conditions.ResultsThe colony morphologies of EBs are white and yellow-coloured colonies, circular to irregular in shape, and entire, and flat margins. Among the 20 purified EBs, 19 isolates were found to be Gram-positive except one i.e., MS2 isolate. The 12 isolates reduced nitrate and 14 isolates produced urease enzyme. The in vitro assay revealed that two isolates, SB4 and RF1, inhibited 56.1% and 55.6% mycelial growth of C. gloeosporioides, respectively. Further, the identity of EBs was confirmed through PCR amplification of the 16S rRNA region resulting in ~1400 bp size amplicons. The sequence analysis of representative 15 isolates revealed that 5 EB isolates viz., SB5, CS2, RG1, RF1, C1 were identified as Bacillus subtilis with >99% sequence identity, two EBs viz., SB3, and CS1 were identified as B. subtilis subsp. subtilis, two EBs viz., SB1, and CS4 were identified as B. licheniformis. The SB2 isolate was identified as Bacillus sp., whereas SB4 as Brevibacillus borstelensis, TH1 as B. velezensis, TH2 as B. tequilensis, CS3 as B. pumilus and MS1 as Micrococcus luteus were identified.ConclusionThe phylogenetic analysis of 16S rRNA sequence revealed eight distinct clades and showed the close clustering of identified species with the reference species retrieved from NCBI GenBank. The current investigation provides the scope for further field evaluations of these endophytic microbes for managing anthracnose disease.